THE STRUCTURE OF DRUG PRESCRIPTION IN ACUTE CORONARY SYNDROME WITHOUT ST SEGMENT ELEVATION ON THE FIRST DAY OF HOSPITAL THERAPY - O. V. Reshetko; N. V. Furman; R. M. Magdeev (Столичная издательская компания, 2016)
Aim. To evaluate the structure of drug prescriptions in acute coronary syndrome (acute myocardial infarction and unstable angina) on the first day of hospital therapy in Saratov city and Saratov region.Material and methods. Retrospective pharmacoepidemiology study was carried out in 1276 patients with acute coronary syndrome (ACS) without elevation ST during first 24 hours.Results. Prescription of drugs with proven efficacy in ACS was higher in Saratov city clinical hospital than this in Saratov municipal hospital or hospitals of Saratov region. There were no significant differences in drug prescriptions in Saratov municipal hospital and hospitals of Saratov region.Conclusion. The first day therapy of ACS depends on hospital type.